Simulation Modeling of Space Missions Using the High Level Architecture - Luis Rabelo; Serge Sala-Diakanda; John Pastrana; Mario Marin; Sayli Bhide; Oloruntomi Joledo; Jorge Bardina (Modelling and Simulation in Engineering)
This paper discusses an environment being developed to model a mission of the Space Launch System (SLS) and the Multipurpose Crew Vehicle (MPCV) being launched from Kennedy Space Center (KSC) to the International Space Station (ISS). Several models representing different phases of the mission such as the ground operations processes, engineered systems, and range components such as failure tree, blast, gas dispersion, and debris modeling are explained. These models are built using different simulation paradigms such as continuous, system dynamics, discrete-event, and agent-based simulation modeling. The High Level Architecture (HLA) is the backbone of this distributed simulation. The different design decisions and the information fusion scheme of this unique environment are explained in detail for decision-making. This can also help in the development of exploration missions beyond the International Space Station.